2017
DOI: 10.1016/j.jdeveco.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Poverty traps, convergence, and the dynamics of household income

Abstract: We design a new method to detect household poverty traps. We apply the method to a unique panel that follows rural Indian households over thirty years. We find no evidence of poverty traps. Most households had annual income growth of over 2 percent, and income mobility is high. We then design and apply a method to detect conditional convergence. We find that upper castes are converging to a level of wealth 3 times as high as disadvantaged castes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
4
10
0
Order By: Relevance
“…The absence of evidence of poverty traps within caste groups in rural India is also consistent with Arunachalam and Shenoy (2017) who use the same data but a different econometric approach based on modelling mean household income growth rate changes.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The absence of evidence of poverty traps within caste groups in rural India is also consistent with Arunachalam and Shenoy (2017) who use the same data but a different econometric approach based on modelling mean household income growth rate changes.…”
Section: Resultssupporting
confidence: 75%
“…The data collection effort followed the same households over decades as part of the Rural Economic and Demographic Survey (REDS) survey and has been used in multiple seminal studies (e.g. Behrman et al, 1999;Foster & Rosenzweig, 2002; and in poverty trap analysis by Arunachalam & Shenoy, 2017). 4 In the processed data, household assets in each period were calculated as the value of buildings, land, farm equipment, animals, non-farm business assets, farm and non-farm inventory, consumer durables, cash and non-cash savings, and the value of loans owed to the household minus loans owed by the household.…”
Section: Context and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Second, empirical studies reported the characteristics of rural income inequality in recent decades. Since rural income inequality is complex, these studies focused on overall regional inequality, and inter-and intra-regional inequality, to explore the space structures [11], trends in changes [12][13][14][15], and driving forces. Third, analyses of factors of income inequality and policy suggestions have been produced.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the interplay between these factors, it is important to systematically explore the rural livelihood-environment nexus.With respect to studies on rural livelihoods and the environment, most researchers have focused on one-sided effects instead of mutual relationships [27][28][29]. Researchers have concentrated on the correlations between rural livelihoods and the environment [30,31], poverty traps [32,33], and the spatial clustering of poor populations [34,35]. However, these studies have mostly been based on a single livelihood indicator (general per capita net income), which is insufficient to capture deeper relationships and might be biased.…”
mentioning
confidence: 99%